HUBUNGAN SARANA PRASARANA DAN PROSES PEMBELAJARAN DENGAN HASIL BELAJAR OLAHRAGA DI SMA NEGERI 16 PEKANBARU - Ridho Yatka Pratama; Agus Sulastio; Kristi Agust (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
PJOK is the main lesson in school. Has an important role for the formation of psychomotor, effective, and cognitive learners. In the PJOK learning process itself there is interaction between students and the environment, students with facilities and infrastructure which will later have an impact on learning outcomes. PJOK learning which is dominated by physical movements is carried out in open spaces or fields with supporting infrastructure. This study uses a quantitative correlation approach with the aim of knowing the relationship between infrastructure and learning processes with learning outcomes. Where is the result of statistical analysis of infrastructure facilities with learning outcomes in the form of rcount 0.617 > rtable 0.224 which means there is a relationship in the